PENERAPAN MODEL PEMBELAJARAN PJBL UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PADA PERKULIAHAN PENGEMBANGAN PEMBELAJARAN TEMATIK - Neza Agusdianita; Ike Kurniawati; Irfan Supriatna; Pebrian Tarmizi (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study aims to describe the application of the project based learning learning model to thematic learning development lectures in the PGSD Study Program FKIP Unib. This course is a course with theoretical and practical credits. This course aims to produce students who are able to plan thematic learning, carry out teaching simulations and evaluate learning. The output of this course is learning tools and videos of implementing learning simulations. This study uses action research methods (Action Research). Classroom action research procedures are: (1) planning, (2) implementation, (3) observation, and (4) reflection. The research instrument is in the form of observation sheets and assessment sheets of learning tools and learning videos. Data were analyzed by descriptive qualitative. The research instrument was the researcher equipped with the course RPS and comprehension ability test sheets. Data analysis technique is descriptive qualitative. The output of this research is publication in a national journal accredited sinta 4 Journal of PGSD Bengkulu University.